Social Finance Instruments to Support B40 and Micro-Enterprises: Determinants of Islamic Financial Institution Employees’ Acceptance - Abd Rasid, Muhammad Faris; Ibrahim, Zuraeda; Baharum, Zafiruddin (Asian Journal of Accounting Perspectives, 2020)
Research aim: This paper identifies factors that significantly influence the acceptance of employees from the Islamic Financial Institution of Social Finance Instruments (SFIs) as tools to provide affordable financing to B40 and micro-enterprises. Design/ Methodology/ Approach: A well-structured survey questionnaire, distributed to 197 IFI employees working in institutions that are located in Selangor and listed by the Central Bank of Malaysia. Research finding: Overall, the findings showed that awareness and knowledge have strong and significant relationships with acceptance, whereas, for demographic factors, only education level and monthly income have a significant relationship with the level of acceptance of SFIs among IFI employees. Theoretical contribution/ Originality: The results revealed that the acceptance level of SFIs among IFI employees has a significant and robust relationship with the level of knowledge that employees possess. This is consistent with the Theory of Planned Behaviour, where individuals’ actions depend on their belief about a particular situation when making decisions on behalf of the institution in which they are employed. Therefore, before any IFI implements the SFI concept, they should be proactive in increasing the level of acceptance by taking the steps needed to equip employees with adequate knowledge to ensure that the objectives of SFIs can be achieved. Practitioner/ Policy implication: In the context of this study, awareness and knowledge among the employees of IFIs must be created in advance for any new concept to be readily accepted before the products been introduced to the public. Research limitation/ Implication: Due to the low response rate, future studies could include all IFIs throughout Malaysia along with other SFIs-related individuals such as investors and educators. Type of article: Research paper Keywords: Social Finance Instruments, B40, Micro-Enterprises, Islamic Financial Institutions, Employees’ Acceptance JEL Classification: G21